Sadiq and the Ramadan Gift - Siman Nuurali (Picture Window Books, 2021)
It's Ramadan! In the spirit of the season, Sadiq and his friends want to give back to their community. The friends band together to raise money to build a new school for children in Somalia. They decide to put on a community iftar as a fund-raiser, but not everyone agrees where their efforts should be spent. Can they find a way to work together?
Keywords: Realistic Fiction -- Realistic Fiction